2011
DOI: 10.1590/s1677-04202011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Flowering and vegetative growth of olive tree submitted to pruning and paclobutrazol application

Abstract: This work focuses on the evaluation of flowering and vegetative growth of olive tree submitted to pruning and paclobutrazol application under field conditions with low temperatures during the winter. Two-years-old olive plant variety Grappolo 575, were submitted to light pruning, removing apical dominance, before treatments application. The treatments were organized in a 4×2 factorial scheme, respective to four PBZ concentrations tested: 0, 200, 400 and 800 mg L-1 of PBZ and two plants groups, with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The plant growth increased as the severity of pruning increased, but the fruit set, and yield decreased Albarracín et al (2017). Pruning resulted in stimulation of emission of vegetative shoots and reduction of flowering Cruz et al (2011). The leaf nutrient status was also affected by the different pruning intensities.…”
Section: Resultsmentioning
confidence: 99%
“…The plant growth increased as the severity of pruning increased, but the fruit set, and yield decreased Albarracín et al (2017). Pruning resulted in stimulation of emission of vegetative shoots and reduction of flowering Cruz et al (2011). The leaf nutrient status was also affected by the different pruning intensities.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Most chiral pesticides are sold as the racemic mixture for some limitations, 5 and only 7% chiral pesticides are marketed as the pure isomer or as an enriched mixture of the active isomer, 6 such as S-metolachlor. [14][15][16][17] Some studies have demonstrated that racemic form and two enantiomers of paclobutrazol have different activity in fungicidal and plant growth. The study on the chiral pesticide is so important that recently there are many researches about the stereoselective behavior.…”
Section: Introductionmentioning
confidence: 99%
“…13 Paclobutrazol has been used widely in agricultural production to delay growth period, inhibit stem elongation, shorten internode, promote bud differentiation, enhance plant resistance, and increase yield. [14][15][16][17] Some studies have demonstrated that racemic form and two enantiomers of paclobutrazol have different activity in fungicidal and plant growth. 12 R-PBZ had the higher fungicidal activity, but S-PBZ was more active as a plant growth regulator.…”
Section: Introductionmentioning
confidence: 99%